Evaluating amount of satisfaction for visit capabilities and infrastructures of Gorgan city in separation of touristic entrance regions - Ahmad, Ahmad Pour; Imani, Bahram; Valizadeh, Zeinab; Torabi, Zabihollah; Rezaali, Mansour; Seryasat, Majid Rahmani; Qelichi, Mohammad Molaei; Shabani, Neda; Azimzadeh, Sarah (Ciência e Natura, 2015)
The general aim of this research is evaluating amount of satisfaction for visit capabilities and infrastructures of Gorgan city in separation of touristic entrance regions. This study is applicable and explanatory-analytical method is used for study. Used statistical community is consisting entered tourists from seven touristic regions to Gorgan. In this study, probabilistic multistage cluster sampling method was used. So after calculation of sample numbers by using Kokeran’s formula, some regions were selected as research sample from all of touristic absorptions and questionnaires randomly were distributed among them and then were gathered. Anova test, Danken test and the mean of visitor’s opinions were employed for analysis of data. Also the graphical output of data was depicted through Arc Map software. The findings of research showed that Gorgan tourists have announced unsatisfaction of themselves about capabilities and touristic infrastructures of this city. Nevertheless among different regions there is a meaningful disagreeability. Finally with consideration to operated evaluations about satisfactory condition of tourists related to capabilities and infrastructures of the city for improving situation, suitable solutions have been offered.